Peran Kepala Daerah dalam Perspektif Ketahanan Nasional Untuk Membangun Pendidikan Politik Masyarakat - Sobirin Malian (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2013)
This paper is motivated by a sense of concern about the decline of moral values and ethics in building political community, particularly in the area. Until now, politics in the region have not been able to make people comfortable and at ease, and yet can be the life of the nation and the state. Whereas in Indonesian politics, it is often assumed by the party of democracy (elections), but it proved to be opening it up to the cult crime of corruption, vote inflation and so forth. Therefore, it is necessary that local leaders are able to bring to the region a good and clean politics. It is necessary in the political culture of the principle of Godhead, this is what distinguishes Indonesian political culture with the political culture of other countries. Conception will be structured as accountable as religious (moral) makes the politicians to be more accountable. For technical, political culture can be built through the party system is not reference material. Focus of study in this paper is the role of the head in the area of national security perspective, especially in efforts to build political education community.